Hephaestus and the island of terror - Holub, Joan; Williams, Suzanne, 1953- (Heroes in training, 2015)
"Fresh off their adventure with Crius's Cronies, the Olympians set out for the island of Lemnos, and there's a reason they receive warnings as they travel: Warriors holding intricate weapons greet them as soon as they come ashore! Then they meet Hephaestus, the leader of the island who they quickly realize is actually one of them--the Olympian they were meant to find. But Hephaestus isn't so sure he wants to leave with the Olympians. After all, life is pretty good on Lemnos, and he loves being in charge of the Sintians, who inhabit the island. The Sintians made him their leader because of his metal-working prowess, and he's been doing his best to keep them safe from Cronus's armies ever since. Hephaestus suggests that if he does choose to go with the Olympians, he could be their leader. But what about Zeus? Not everyone is convinced he is still up for the job" --